Krigsmuseets kulturarvsbevaring og det dansk-baltiske sikkerheds- og forsvarsmæssige samarbejde i 1990’erne. Kulturarvsbevaring fra en overset del af det danske internationale engagement - Christensen, Jens Ole (Fra Krig og Fred, 2026)
The Danish War Museum is the central museum for war and military history in Denmark. It is a museum for military- and culturel history in a broad sense. In an overall view, the article outlines the work of the Danish War Museum, regarding the securing of culturel heritage, from danish war and military history. And more specific, the danish security policy and defence cooperation with the Baltic countries Estonia, Latvia and Lithuania, which was a significant part of the Danish international engagement in the 1990s. In a more specific view, the article outlines, on the one hand, the basic ideas of the work of securing of cultural heritage at the museum, and on the other hand, the basic lines of the Danish security policy and defence cooperation with the Baltic countries. Hereafter ending up with presenting some of the museums specific collection projects regarding the cooperation with the baltic countries. The Danish War Museum has since the 1990s placed much greater emphasis on research, and has completely rethought its work of securing cultural heritage, which now has taken the character of actively outreaching, contemporary, research-based and problem-oriented access. The cooperation with the Baltic countries, has in Danish history writing, been described as the most succesfull, and in the long term, most important part of the Danish international engagement, in the 1990s. The museum has tried to ‘capture’ this ‘big story’ in a number of ‘small stories’ in the sense of a number of specific collection projects, for example seen in a collection of items from, and knowledge about, a number of danish and baltic soldiers. Soldiers that as ‘small stories’ puts face to the ‘big story’.